Frequency of Occupational Bloodborne Infections and Sharps Injuries among Polish Paramedics from Selected Ambulance Stations - Ganczak, Maria (Int J Environ Res Public Health, 2020)
To evaluate the prevalence of bloodborne infections (BBIs) and assess the incidence and selected risk factors for sharps injuries (SIs), a cross-sectional serosurvey was performed between December 2018 and October 2019 among 286 paramedics (76.5% males; mean age, 37 years) from 17 randomly selected ambulance stations in the West Pomeranian region of Poland. An ELISA system was used to detect anti-HBc, anti-HCV, and anti-HIV. HBV vaccination uptake was 95.6%; 7.3% (95% CI: 4.6–11.0%) paramedics were anti-HBc positive, and anti-HCV/anti-HIV seropositivity was not reported. Almost one-fourth of paramedics reported having had ≥1 SI during the preceding year (Me = 6.0, range 1–100). Most recent exposures primarily took place during an emergency procedure (76.7%), in an ambulance (45.2%), caused by hollow-bore needles (73.8%), and were not reported (50.0%). Additionally, 52.2% of paramedics reported needle recapping, and 52.6% did not use safety engineered devices (SEDs) at work. Mean knowledge score was low (2.6 ± 1.7); 3.4% had never participated in infection-control (IC) training, and those not trained were more likely to suffer a SI (odds ratio (OR) 4.64; p = 0.03). Due to frequent SIs, of which half are unreported, paramedics remain at risk of acquiring occupational BBIs. SI risk could be reduced by providing training on IC procedures, ensuring better compliance with safe work practices, and supplying more SEDs.